Analisis Relevansi Pendidikan Kewirausahaan dan Lingkungan Kampus Terhadap Minat Berwirausaha Mahasiswa Perguruan Tinggi di Jawa Barat, Indonesia - Anggaraeni Permatasari; Rendika Nugraha; Ihsan Hadiansah (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2018)
Entrepreneurship ecosystem development is new concept to support entrepreneurship education in higher education institution. The objective of this research is to analyze the relevance between entrepreneurship education and university environment to encoura ge student entrepreneurial intention in higher education institution. Higher education institution is university or higher institution in West Java, Indonesia, that have business faculty or entrepreneurship subject in their study of program, also supportin g by conducive environment that liven up entrepreneurial activity. The population of the research are students in University/Institution in surrounding West Java Area that already learned entrepreneurship subject and operated business simulation in real wo rld. Quantitative method by survey is used for this research. Data collection is using questionnaire with likert scale 1 - 7. Structural Equation Modelling (SEM) is use to analyze data to justify the significancy of the model. The novelty of this research is to see the relationship between entrepreneurial education and campus environment toward student entrepreneurial motivation and intention as one holistic system that influence each other. Also, the results of this research can be used to development repreneurial higher education institution ecosystem model in Indonesia